2012
DOI: 10.1038/ncomms1725
|View full text |Cite
|
Sign up to set email alerts
|

Interpolar microtubules are dispensable in fission yeast meiosis II

Abstract: The mitotic spindle consists of two types of microtubules. Dynamic kinetochore microtubules capture kinetochores, whereas stable interpolar microtubules serve as the structural backbone that connects the two spindle poles. Both have been believed to be indispensable for cell division in eukaryotes. Here we demonstrate that interpolar microtubules are dispensable for the second division of meiosis in fission yeast. Even when interpolar microtubules are disrupted by a microtubule-depolymerizing drug, spindle pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The latter strain appeared suitable for use in combination with severe mutation backgrounds that affect microtubule formation because the former GFP-Atb2 construct occasionally showed synthetic growth defects when combined with some mutations. Strain Z2-GFP-Atb2 has been used to elucidate previously unknown microtubule behaviors in various aspects of mitosis [26] and meiosis [27], [28], [29], [30]. We therefore prepared a three-colored strain expressing GFP-Atb2, Nup40-mCherry [31], and Sfi1-CFP (cyan fluorescent protein) [32] to monitor the behavior of microtubules, the nuclear envelope, and the SPB, respectively ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The latter strain appeared suitable for use in combination with severe mutation backgrounds that affect microtubule formation because the former GFP-Atb2 construct occasionally showed synthetic growth defects when combined with some mutations. Strain Z2-GFP-Atb2 has been used to elucidate previously unknown microtubule behaviors in various aspects of mitosis [26] and meiosis [27], [28], [29], [30]. We therefore prepared a three-colored strain expressing GFP-Atb2, Nup40-mCherry [31], and Sfi1-CFP (cyan fluorescent protein) [32] to monitor the behavior of microtubules, the nuclear envelope, and the SPB, respectively ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of spindle MTs has infrequently been studied explicitly. In one case, fission yeast spindle MTs extending from each pole were shown to be dispensable for meiotic spindle function (Akera et al, 2012); however, in other systems, spindle MTs have a more pronounced role. Depletion of spindle MTs from Xenopus egg extract spindles by addition of a tubulin-sequestering protein revealed a role for spindle MTs in establishing proper MT dynamics within the k-fiber as well as for maintaining spindle size (Houghtaling et al, 2009).…”
mentioning
confidence: 99%
“…Hence, it remains possible that the diffusion of several nuclear proteins in meiosis II participates to this non-canonical chromosome segregation event. A second difference between meiosis I or II is the presence in meiosis II of the forespore membrane, which encapsulates the nucleus and produces forces for cell division (Akera et al, 2012). Markedly, it has been shown that interpolar MTs were dispensable in meiosis II for spindle pole separation (Akera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A second difference between meiosis I or II is the presence in meiosis II of the forespore membrane, which encapsulates the nucleus and produces forces for cell division (Akera et al, 2012). Markedly, it has been shown that interpolar MTs were dispensable in meiosis II for spindle pole separation (Akera et al, 2012). Finally, it is formally possible that the lack of DNA replication prior meiosis II might change the requirement for condensin activity during the subsequent division.…”
Section: Discussionmentioning
confidence: 99%